Antagonistic Role Of Fungal Biocontrol Agents For Sustain Able Management Of Rice Blight Caused By Curvularia Lunata (Applied Biological Research, 2022)
Plant growth promoting fungi (PGPF) have received much attention in  recent past due to their plant growth promoting ability and antagonistic  activity against disease causing pathogens. They can suppress the pathogen  directly by antagonistic mechanism or indirectly by inducing systemic  resistance. The present study was aimed to assess the biocontrol efficacy of  rhizospheric fungi, isolated from rice fields, against rice blight pathogen Curvularia lunata. Dual culture method was used to assess the antagonistic  potential of isolates against the pathogen. Out of the 20 isolates, 14 isolates  exerted positive effects against C. lunata in dual culture. SEM studies of interacting zone between the pathogen and isolates in dual culture revealed  the mycoparasitic property of Trichoderma aureoviride TaN16 and  Aspergillus niger AnD6 against the pathogenic fungus. These two isolates were found associated with HCN production. Three fungal isolates viz., T.  aureoviride TaN16, T. yunnanense TaN17 and Talaromyces purpureogenus  TpG11 triggered the induction of defense enzymes like phenylalanine  ammonia-lyase, polyphenol oxidase and peroxidase. The study revealed that  the rhizospheric fungal isolates having biocontrol potential can serve as  alternative to chemical fungicides under integrated disease management.
Keywords: Antagonism; defense enzymes; hydrogen cyanide; plant growth promoting fungi; rhizosphere